WARIS HUTANG PIUTANG DALAM TRADISI HANTARAN PERKAWINAN PERSPEKTIF HUKUM ISLAM: (Studi Kasus di Desa Sumberejo, Kecamatan Banyuputih, Kabupaten Situbondo) - Siti Ayu Rahayu; Dyah Ochtorina Susanti; Dominikus Rato; Ainun Najib (LP2M Universitas Ibrahimy, 2023)
The culmination of the wedding procession was the Walimatul Urs, or the wedding reception. Giving innate when celebrating wedding receptions among the community was commonplace, even though the status of the gift was under the customs that apply in that area. Likewise in Sumberejo Village, Banyuputih District, Situbondo Regency. Problems arise when innate at the wedding reception celebration is counted as a form of the loan agreement. Therefore, the researchers tried to describe how the tradition was inherited when the wedding reception was held in Sumberejo Village, Banyuputih District, Situbondo Regency. The research method used was a qualitative method using descriptive analysis. Based on the study's results, the default status at a wedding reception in Sumberejo Village, Banyuputih Sub-District, Situbondo Regency, was counted as Sodakoh, measured as a gift, and counted as accounts payable. The innate tradition during wedding receptions was counted as accounts payable can positively and negatively impact the event organizer. According to Islamic Law, the issue of inheritance of debts owed to debtors at a wedding reception in Sumberejo Village was included in the Tirkah criteria that must be received and paid for by the heirs.